Comparison the effects of gabapentin and oxazepam on sleep quality, anxiety, and pain in unstable angina patients admitted to coronary care unit of Hazrat Rasool Akram Hospital - Mohammadjavad Parvaresh; Mirfarhad Ghalebandi; Kaveh Alavi; Shekoufeh Hajsadeghi; Atefeh Ghanbari Jolfaei (Advanced Biomedical Research, 2022)
Background: This study aimed to compare the efficacy of gabapentin and oxazepam on sleep quality, the severity of anxiety, and pain level in patients admitted to the coronary care unit (CCU). Materials and Methods: This double-blind randomized clinical trial was done on the patients with unstable angina (UA) admitted to the CCU of Hazrat Rasool Akram Hospital in Tehran. A total of 56 patients were entered the study and randomly divided into two groups of 26. The first group was given a gabapentin capsule at a dose of 300–1200 mg/day, and the second group was given 10–20 mg of oxazepam tablets per day until hospitalization in the CCU. On the first and 4th days of hospitalization, Groningen sleep quality score (GSQS), Beck Anxiety Inventory, and severity of pain experienced by Visual Analogue Scale were recorded, and the mean frequency of chest pains was calculated in 24 h during the first 4 days. The amount of drug (morphine) prescription in CCU also compared between the two groups. Results: There was no significant difference in GSQS scores between both groups. The mean score of Beck's anxiety scale did not differ significantly between the two groups. However, the incidence of chest pain was significantly lower in the gabapentin-receiving group than in the oxazepam-receiving group (<0.001). The days that the patients experienced chest pain were significantly less in the gabapentin-receiving group than in the oxazepam-receiving group (<0.001). Conclusion: The results of our study showed that gabapentin compared to oxazepam could significantly reduce chest pain in patients with UA.